Enteric Helminths Promote Salmonella Coinfection by Altering the Intestinal Metabolome. (25th March 2017) - Reynolds, Lisa A.; Redpath, Stephen A.; Yurist-Doutsch, Sophie; Gill, Navkiran; Brown, Eric M.; van der Heijden, Joris; Brosschot, Tara P.; Han, Jun; Marshall, Natalie C.; Woodward, Sarah E.; Valdez, Yanet; Borchers, Christoph H.; et al.
Summary: Intestinal helminth infection increases small-intestinal colonization by Salmonella, which occurs independently of the induction of T regulatory or Th2 cells following helminth infection. Helminth infection disrupts the intestinal metabolome, and the resulting shift in metabolites directly enhances Salmonella virulence. Abstract: Intestinal helminth infections occur predominantly in regions where exposure to enteric bacterial pathogens is also common. Helminth infections inhibit host immunity against microbial pathogens, which has largely been attributed to the induction of regulatory or type 2 (Th2) immune responses. Here we demonstrate an additional 3-way interaction in which helminth infection alters the metabolic environment of the host intestine to enhance bacterial pathogenicity. We show that an ongoing helminth infection increased colonization by Salmonella independently of T regulatory or Th2 cells. Instead, helminth infection altered the metabolic profile of the intestine, which directly enhanced bacterial expression of Salmonella pathogenicity island 1 (SPI-1) genes and increased intracellular invasion. These data reveal a novel mechanism by which a helminth-modified metabolome promotes susceptibility to bacterial coinfection.